A FEMINIST PERSPECTIVE OF THE WOMANSTRUGGLE IN A NOVEL THE COLOR PURPLE - Pebriani, Brigda; Amrina Sari, Riski (LPPM STBA Pontianak, 2024)
This study aims to look at injustice, violence, and discrimination from men towards women and their environment with a review of multicultural feminism, and to identify what resistence and struggles conducted by the main characters to defend their rights. This study used descriptive qualitative research. The data of this study was utterances from the characters. The result showed that there are four problems faced by the women in the novel they are; in martial status where the wife must be good wife when they obey what the husband’s rule. Race issues to be the second problem, educations environment, and child status in the family. Then, the womens struggles in this novel are doing what she likes to show she can doing something without her her husband and arise from the oppressed to get freedom, and she get a job even though she always discriminated by white people. The understanding of multicultural feminism which emphasizes multicultural aspects, really upholds diversity. There should be no more violence against women, acts of injustice, and discrimination in any form. Everyone should be treated equally and should receive the same respect. And women also have the right to be free and get the rights they deserve as a woman.